Association between functional capacity and functional health literacy among older adults (Research, Society and Development, 2021)
Objective: To verify whether there is an association between functional capacity and functional health literacy among                 older adults assisted by the Family Health Strategy. Method: Exploratory descriptive study with a cross-sectional                 quantitative approach, carried out in the coverage area of ten Family Health Strategy teams, with a total of 350 older                 adults. Data was collected through a socio-demographic questionnaire and the application of validated instruments to                 measure functional capacity and functional health literacy. Data was collected from July to December 2017.                 Descriptive statistical analysis and chi-square, ANOVA and Spearman correlation tests were performed. Results:   There was no relationship between basic activities of daily living and functional health literacy. There was a positive        correlation between the scores on the scales of instrumental activities of daily living and functional health literacy.     Conclusion: There is an association between functional capacity and functional health literacy regarding instrumental       activities of daily living.